Речные раки (Crustacea, Astacidae) Советского Союза. Сообщение IV. О времени и месте вселения евро-азиатских речных раков в пресные воды - Бродский, С.Я. (Вестник зоологии, 1976)
The observations of crawfish behaviour were carried out in artificial water bodies with varying existence conditions. Migration of the western-palearctic Astacidae species to fresh waters in the Ancient Old Pontian Black sea epoch is substantiated. The immigration theory of the Caspian fauna origin (including Astacidae) in the Pontoazovian area is confirmed.